2021
DOI: 10.1016/j.eclinm.2021.101030
|View full text |Cite
|
Sign up to set email alerts
|

Kidney function and cancer risk: An analysis using creatinine and cystatin C in a cohort study

Abstract: Background: We examined whether an increased risk of cancer incidence and death is associated with kidney function and albuminuria and whether the risk is more readily identified when kidney function is estimated using cystatin C. Methods: Participants were from UK Biobank (recruitment spanning 2007À2010), excluding those with a prior diagnosis of cancer. Estimated glomerular filtration rate (ml/min/1.73m 2 ) was calculated using creatinine (eGFRcr), cystatin C (eGFRcys) and creatinine-cystatin C (eGFRcr-cys).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 36 publications
4
41
0
Order By: Relevance
“…Furthermore, a higher cystatin C concentration was also associated with incident prediabetes 30 , hypertension 31 , coronary heart disease 32 , 33 , myocardial infarction 8 , and stroke 8 , 34 , all of which could contribute to increased mortality. With regard to cancer mortality, there is very limited evidence examining the association of cystatin C with cancer mortality 18 . Our study indicated that a higher cystatin C concentration is associated with an increased risk of cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a higher cystatin C concentration was also associated with incident prediabetes 30 , hypertension 31 , coronary heart disease 32 , 33 , myocardial infarction 8 , and stroke 8 , 34 , all of which could contribute to increased mortality. With regard to cancer mortality, there is very limited evidence examining the association of cystatin C with cancer mortality 18 . Our study indicated that a higher cystatin C concentration is associated with an increased risk of cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
“…CKD has also been shown to contribute to cancer morbidity and mortality 14 16 . Nonetheless, evidence regarding the relationship between cystatin C concentration and cancer mortality is very limited 17 , 18 . In addition, whether the associations of cystatin C concentrations with mortality vary by potential modifying factors, such as gender and age group, remain controversial 13 , 19 , 20 , which may have important implications for the application of cystatin C.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another Korean study found that the overall incidence of cancer in patients with CKD was >1000/100,000 person-years [ 19 ]. A third study from the United Kingdom also found that a lower GFR was associated with an increased risk of incident cancer [ 20 ]. In contrast, other studies have not found an increased risk of cancer with lower eGFR [ 7 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were seen in an Australian study which showed increased cancer mortality in patients with an estimated glomerular filtration rate < 60 mL/min/1.73 m 2 [ 28 ]. A large study from the UK also suggested that an eGFR <90 ml/min/1.73m 2 was associated with increased cancer mortality [ 20 ]. This is not particularly surprising, since treatment modification may commonly be needed in patients with decreased eGFR to decrease toxicity of chemotherapy agents.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have shown that CKD increases cancer mortality [ 4 , 5 ]. Specifically, CKD is associated with an increased risk of cancer death among kidney cancer patients [ 6 ]. The association between CKD and cancer mortality remained evident after adjusting for chemotherapy and patients’ factors, including performance status [ 7 ].…”
Section: Introductionmentioning
confidence: 99%